Automatic Theft Detector and Locker Device for Automatic Teller Machine - R.B, Vijayshree; H.V, Brungesh.; .K.R, Goutham; B, Arjun.; .Madhaw, Lohith.N; K, Ashok (IJRDO - Journal of Electrical And Electronics Engineering, 2016)
Now a days, as we all know, people depend more on ATM than banks for transaction of money. Banks are also trying to fulfill the need of the people, as transaction through ATM is easier than in banks. But the problem occurs here. As ATM contains plenty of money filled in it, it will be a great stuff to rob for robbers. Now a day’s robbery of money in ATM has been a very huge headache for banks even though they have tight security and CC Cameras. So, we have built this device which makes an Automatic Teller Machine [ATM] even more secured. Our device ‘Automatic Theft Detector and Locker Device [ATDLD] is a trap for robbers from which they cannot escape. This device consists of a simple and low expensive circuit. The body of the ATM will be internally connected with wires and plugs and further connected to the circuit. When the robbers try to open the body of the ATM the connected plugs will break. Once the plug gets disconnected the GSM module sends a message to Police station, Security and Bank supervisors. Within few seconds the motor locks the door of the room and makes the thief to remain inside until the security arrives. Once the door is shut the alarm which is kept outside the room starts buzzing and intimates the public about the thief inside the ATM room.